ONO Epistemologies—Resounding the “Bleeding Haints”: A Noisy Conversation between P. Michael Grego, travis, and Shannon Rose Riley of ONO - Riley, Shannon Rose; Grego, P. Michael (Performance Matters, 2020)
To resound means not only to make a loud, prolonged sound but also to send the soundings back—whether to their source(s) or other listeners, as if in a kind of dialogical loop. In this article, P. Michael, travis, and Shannon Rose Riley engage in a resounding conversation on the performance practices of the sonic subaltern as exemplified in their work as ONO. They discuss “bleeding haints,” “ghosted tracks,” and how their work resounds/re-members erased histories. They also begin to flesh out what travis calls “the colors of Noise” regarding how the Black body is always already a kind of “Noise upon the USAmerican landscape.” These are ONO epistemologies.